Religion in the Perspective of the Punk Community: Phenomenological Study on Punk Community Members in Tasikmalaya City - Regita Cahya Karima (UIN Sunan Gunung Djati Bandung, 2022)
The survey results showed that all Punk community members were Muslim, and 75 per cent were graduates of Islamic boarding schools with broken homes, poverty and lifestyle backgrounds. Based on observations in the field, their lives, especially those who graduated from Islamic boarding schools, are now not just able to enjoy a free life. However, based on freedom, they live wild lives and behave in strange ways, starting from extortion, drugs, and committing sexual crimes. In this study, the authors focus on religion from the perspective of the Punk community in Tasikmalaya City. These two theories and methods are appropriate for exploring a person's reality in depth based on their experience. The approach used in this research is qualitative. In this study, the authors used phenomenological theory and the construction of social reality with qualitative methods. The researchers employed a qualitative approach to address the problem in this study; The researcher obtained information that yielded descriptive data in the form of written or spoken words and through observation of the subject's behavior. The analysis results obtained two categories of religious understanding: three members of the Tasikmalaya City Punk community and pesantren alums understood religion as a nail. In contrast, two high school graduates of informants understood religion as a cage. However, this understanding differs from Punk community members in Tasikmalaya City